Change in Compliance of Staff at 4 Vietnam Universities after the Enactment of Smoke-free Environment Decree. (December 2020) - Nguyen, Ngoc Bich; Capra, Mike; Johnstone, Kelly; Vu, Hoang Lan; Tran, Vu; Nguyen, Minh Tham; Nguyen, Kim Ngan; Cook, Margaret
Background: The Tobacco Control Law in Vietnam was adopted in 2012 and came into force from May 2013, followed by a number of guiding sub-law legal documents. Smoke-free campus policy in university is considered an important measure to protect people from secondhand smoking as well as staffs and students will be in favour of the policy. Furthermore, there has been evidence suggested that smoke-free policy had positive impact on active smoking as well as anti-smoking attitude. Methods: A cross-sectional self-administered study of staff at 4 universities were conducted in 2 phases, Phase 1 as early introduction of the Law (n = 900) and Phase 2 as 1-year post (n = 885). Demographics, tobacco consumption, compliance status and compliance with awareness towards the campus smoking regulations were assessed in both phases. Results: Daily smoking prevalence decreased significantly ( P  < .05) 1 year after implementing the smoke-free policy, while a significant increase in occasional smoking ( P  < .01). Compliance of staff to the regulation the campus should be indoor smoke-free was significantly increase at Phase 2 compared to Phase 1, however participants reported there would be places on campus that smokers frequently violated the smoke-free regulations. Conclusions: The study indicated a significant positive change in compliance of staff at the 4 universities after the implementation of the Tobacco Control Law, included the smoke-free policy. Although the prevalence of tobacco smoking in this study was low, the proportion of respondents who reported to reduce infringement the smoke-free policy suggests support for staff smokers would be beneficial. Raising awareness and enforcement is likely to enhance the long-term outcomes of the implementation of smoke-free environment.